Distributed category‐specific recognition‐memory signals in human perirhinal cortex. Issue 4 (19th October 2015) - Martin, Chris B.; Cowell, Rosemary A.; Gribble, Paul L.; Wright, Jessey; Köhler, Stefan
ABSTRACT: Evidence from a large body of research suggests that perirhinal cortex (PrC), which interfaces the medial temporal lobe with the ventral visual pathway for object identification, plays a critical role in item‐based recognition memory. The precise manner in which PrC codes for the prior occurrence of objects, however, remains poorly understood. In the present functional magnetic resonance imaging (fMRI) study, we used multivoxel pattern analyses to examine whether the prior occurrence of faces is coded by distributed patterns of PrC activity that consist of voxels with decreases as well as increases in signal. We also investigated whether pertinent voxels are preferentially tuned to the specific object category to which judged stimuli belong. We found that, when no a priori constraints were imposed on the direction of signal change, activity patterns that allowed for successful classification of recognition‐memory decisions included some voxels with decreases and others with increases in signal in association with perceived prior occurrence. Moreover, successful classification was obtained in the absence of a mean difference in activity across the set of voxels in these patterns. Critically, we observed a positive relationship between classifier accuracy and behavioral performance across participants. Additional analyses revealed that voxels carrying diagnostic information for classification of memory decisions showed category specificity in their tuning for faces when probed with an independent functional localizer in a nonmnemonic task context. These voxels were spatially distributed in PrC, and extended beyond the contiguous voxel clusters previously described as the anterior temporal face patch. Our findings provide support for proposals, recently raised in the neurophysiological literature, that the prior occurrence of objects is coded by distributed PrC representations. They also suggest that the stimulus category to which an item belongs shapes the organization of these distributed representations. © 2015 Wiley Periodicals, Inc.